PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN IKLIM ORGANISASI TERHADAP SEMANGAT KERJA KARYAWAN PADA PT. MULTISARANA AGRO LESTARI PEKANBARU - Pasaribu, Sandi Pradana; Indarti, Sri; Rifqi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted at PT. Multisarana Agro Lestari Pekanbaru. The study is quantitative descriptive type kolerasional. The sample in this study are numbered as many as 51 people. Data collection techniques with interviewand questionnaire. Multiple linear regression analysis using SPSS version. The regression test Partially that each independent variables studied (leadership, work environment and climate organization) has an influence on the dependent variable (morale) it was shown by the results that the leadership variablesignificant effect on employee morale, workplace environment variable significant effect on employee morale, while the organizational climate variables significant effect on employee morale PT. Multisarana Agro Lestari Pekanbaru. And whilethe simultaneous regression test showed that the independent variables studied (leadership, work environment and climate organization) has an influence on the dependent variable (morale). The magnitude of the effect caused by the threeindependent variables namely 56.9% while the remaining 43.1% is influenced by other variables not examined in this study.Keywords: Leadership, Work Environment, Organizational Climate and Employee Morale